2019
DOI: 10.1109/tcomm.2018.2880204
|View full text |Cite
|
Sign up to set email alerts
|

Throughput-Based Design for Polar-Coded Modulation

Abstract: Typically, forward error correction (FEC) codes are designed based on the minimization of the error rate for a given code rate. However, for applications that incorporate hybrid automatic repeat request (HARQ) protocol and adaptive modulation and coding, the throughput is a more important performance metric than the error rate. Polar codes, a new class of FEC codes with simple rate matching, can be optimized efficiently for maximization of the throughput. In this paper, we aim to design HARQ schemes using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…When the channel quality is improved, the used rate of user should be increased for higher efficiency. Based on the evaluated throughput, efficient search algorithms, such as golden‐section searching method [16], is employed to determine the optimal rates. With the known channel state estimation, adaptive CC of polar code is realized.…”
Section: Adaptive Optimization For Transmission Efficiencymentioning
confidence: 99%
“…When the channel quality is improved, the used rate of user should be increased for higher efficiency. Based on the evaluated throughput, efficient search algorithms, such as golden‐section searching method [16], is employed to determine the optimal rates. With the known channel state estimation, adaptive CC of polar code is realized.…”
Section: Adaptive Optimization For Transmission Efficiencymentioning
confidence: 99%
“…For simplicity, we let the maximum number of transmissions K be 2 in this section. It can be extended to arbitrary K. Note that in some literature [8], [9], [17], [25] the goal is to maximize the throughput. As shown in [8], the throughput of an HARQ system can be written as…”
Section: A Optimization Problemmentioning
confidence: 99%
“…The authors in [24] showed that correlated channels may yield higher throughput than independent channels for HARQ. HARQ code design for polar codes was studied in [25], and HARQ code design for low-density parity-check codes was studied in [26]. In [27], the authors surveyed HARQ code design for turbo codes.…”
Section: Introductionmentioning
confidence: 99%
“…When using HARQ or adaptive SCLD technique, throughput is an improtant metric to design coding scheme, where throughput of a decoder can be defined as [23] η = R(1 − P fer ) (15) where P fer is the FER of the decoder. In Fig.…”
Section: Throughput Of the Proposed Schemementioning
confidence: 99%